2004
DOI: 10.1073/pnas.0400663101
|View full text |Cite
|
Sign up to set email alerts
|

Molecular sorting by stochastic resonance

Abstract: To sort a targeted species from a mixture, we introduce a procedure that relies on the enhancement of its effective diffusion coefficient. We use the formation of a host-guest complex between ␣-cyclodextrin and a dye to evidence the dye dispersion when the medium is submitted to an oscillating field. In particular, we demonstrate that the effective diffusion coefficient of the dye may be increased far beyond its intrinsic value by tuning the driving field frequency in the stochastic resonance regime. We use th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…This expression constitutes one of the main results of the present work. It extends in particular the results known in absence of adsorption and desorption at the wall [12] (recovered in the limits Y → 0 or Z → ∞) and in the case of an infinitely well stirred limit in the transverse direction (corresponding to X → 0) [10,12,14,15], with an adsorption rate 2k a /L.…”
Section: Case Of a Sinusoidal Velocity Fieldsupporting
confidence: 77%
See 1 more Smart Citation
“…This expression constitutes one of the main results of the present work. It extends in particular the results known in absence of adsorption and desorption at the wall [12] (recovered in the limits Y → 0 or Z → ∞) and in the case of an infinitely well stirred limit in the transverse direction (corresponding to X → 0) [10,12,14,15], with an adsorption rate 2k a /L.…”
Section: Case Of a Sinusoidal Velocity Fieldsupporting
confidence: 77%
“…However, in the important case where the components of the mixture have different kinetic rates k a and k d but similar partitioning coefficients k a /k d L, such a separation is impossible with a stationary flow, since P stat (b), hence x(t) , of all species are similar. As we now proceed to show, efficient sorting can nevertheless be achieved in this case by resorting to an oscillatory flow and exploiting the stochastic resonance between the exchange kinetics and the flow, thereby extending the idea put forward by Alcor et al in another context [14,15].…”
Section: Case Of a Stationary Velocity Fieldmentioning
confidence: 66%
“…Recently, the great interest in nanofluidic devices and in the transport in heterogeneous porous media has also raised the issue of the relevance of models which do not take into account these sorption processes. Moreover, it was recently shown that stochastic resonance between these processes and some external field may be of practical importance, e.g., for molecular sorting [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we exploit the unique discriminative kinetic parameters [13,14] of photoswitchable fluorescent probes to explore an alternative approach for selective and quantitative imaging. Our strategy relies on a periodically modulated monochromatic illumination with average light intensity and modulation frequency tuned so that the amplitude of the outof-phase fluorescence response extracted from phase-sensitive detection results only from a fluorescent probe of interest, thus enabling extraction of its signal from a complicated fluorescence signal composed of several emitters.…”
mentioning
confidence: 99%